Investigation of Metal and Nonmetal Ion Migration Through Phosphogypsum - O. C. Carter; B. J. Scheiner (Society for Mining, Metallurgy & Exploration, 1992)
The Bureau of Mines is investigating the effects of rainfall and gypsum/cooling pond water on the rate of metal and nonmetal ion mobility through phosphogypsum stacks located in central Florida. Since leachate contains metal and nonmetal ions that have the potential for migration into surface and groundwater, laboratory column leach tests were conducted. Synthetic rainwater was passed through the column and metal and nonmetal ion migration was monitored. Similar experiments were conducted using a number of synthetic solutions which simulated a number of different compositions of gypsum/cooling pond water. Results indicate that within the first five pore volumes most of the mobile metals and nonmetals were removed.